2020
DOI: 10.1111/tri.13592
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis of kidney transplant recipients with aorto‐iliac calcification: a systematic review and meta‐analysis

Abstract: The prognosis of kidney transplant recipients (KTR) with vascular calcification (VC) in the aorto-iliac arteries is unclear. We performed a systematic review and meta-analysis to investigate their survival outcomes. Studies from January 1st, 2000 until March 5th, 2019 were included. Outcomes for meta-analysis were patient survival, (death-censored) graft survival and delayed graft function (DGF). Twenty-one studies were identified, eight provided data for meta-analysis. KTR with VC had a significantly increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…The literature on abdominal aorta calcification (AAC) assessment by plain pelvic X-ray or dual X-ray absorptiometry, using visual grading scales, is more extensive [13]. Studies evaluating this method showed results similar to our findings, with significant associations of a high-AAC with all-cause mortality and cardiovascular events in multivariable Cox regression analyses [12,20,21].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The literature on abdominal aorta calcification (AAC) assessment by plain pelvic X-ray or dual X-ray absorptiometry, using visual grading scales, is more extensive [13]. Studies evaluating this method showed results similar to our findings, with significant associations of a high-AAC with all-cause mortality and cardiovascular events in multivariable Cox regression analyses [12,20,21].…”
Section: Discussionsupporting
confidence: 84%
“…Prior studies have identified imaging-proven vascular calcification as a prognostic factor for inferior survival and cardiovascular events in kidney transplant recipients [12,13]. For the applied imaging studies, a distinction can be made between coronary artery calcification (CAC) and aorto-iliac calcification, as well as between assessment of calcification prior to and after transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…While there are data to formulate life prognosis for patients with heart disease or femoropopliteal disease, specific survival data in patients with iliac disease are scarce. There is some evidence that severe calcifications in the infrarenal aorta and the iliac arteries are associated with higher mortality with a functioning graft, major vascular events after kidney transplantation, 4 and cardiovascular morbidity and mortality in the dialysis patient population 5‐11 …”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that severe calcifications in the infrarenal aorta and the iliac arteries are associated with higher mortality with a functioning graft, major vascular events after kidney transplantation, 4 and cardiovascular morbidity and mortality in the dialysis patient population. [5][6][7][8][9][10][11] Conventional arteriograms have not had a significant role as a screening tool in kidney transplant evaluation. CT angiograms have replaced conventional angiograms, as they are less invasive, but they still require intravenous contrast administration and deliver significant radiation exposure.…”
Section: Ta B L Ementioning
confidence: 99%
“…The vessels of the pancreatic graft are anastomosed to the recipient's iliac vessels. It is known that calcification of these vessels can increase graft loss and even mortality risk post-transplantation [63,64]. Unexpectedly finding a calcified vessel intra-operatively may delay the ischemic time of the graft organ and the length of the operation.…”
Section: Preoperative Vascular Assessmentmentioning
confidence: 99%